Report of The Committee of The National Development Council on Population - Planning Commission (Planning Commission, 1992)
India's population, which was recorded as 844.3 millions by the 1991 Census, has grown at an annual average of over 2 per cent during the last four decades. This means an addition of about 18 million people to the country's population per year.
Planning Commission Government of India
Planning Commission Government of India